Inventory of the vascular flora of the alkaline fen “Torbiera di Lipoi” (Veneto, northern Italy) - Katia Zanatta; Cesare Lasen; Alberto Scariot; Juri Nascimbene (Italian Botanist)
On the basis of literature, and herbarium data and new field research, we provide a diachronic floristic inventory of a small alkaline fen meadow close to the southern border of the Dolomiti Bellunesi National Park (Veneto, N-Italy), whose toponymal is “Torbiera di Lipoi”. Overall, 319 infrageneric taxa were listed. Results indicate that, despite natural reforestation triggered by the abandonment of the traditional management of the fen, most of the fen-related vascular species still occur, including red-listed species, although their populations have probably decreased over time. Moreover, alien species are still a minor component of the flora, occurring in small scattered populations. However, there are signals of vulnerability, and probably the current vascular flora reflects a previous situation in which fen-related habitats were much larger than today. This urgently claims for active maintenance of the small open areas that still exist to counteract extinction debt dynamics.